ANALISIS PERTUMBUHAN HARGA SAHAM DI BURSA EFEK INDONESIA PADA SAAT PANDEMIK COVID 19 - Vida Ramayani Siregar; Sinta Kumala Sari; Syarifullah Hidayat; Cindy Adelia; Dewi Purnama Sari (Al-Sharf: Jurnal Ekonomi Islam, 2020)
Macro economics is a study about activities of economy in a country. The indicator of macro economics are inflation, unemployment, and growth of economics. The aim of this research is to analyze. The factors which influence the growth of economics in Indonesia at the time of the co-pandemic 19. The factors are inflation and growh of economics at the time of the co-pandemic 19. Thish research using multiple regression method Ordinary Least Squares (OLS) which data book from 2011-2015 per semester. Finally this research shows only unployment variable influance significantly to growth of economics with probability 0,0191. While the inflation show that the probability 0,1955. It means there is no influence significantly between inflation to growth economics. High of inflation, interest rate and depreciation of IDR to USD will decrease the  stock price. The study aimed to know the effect of macroeconomic factor, inflation, exchange rate, and interest rate on IDX Composite in IDX. This study used multiple linear regression. Result show inflation variable have a significant effect IDX Composite as well as Exchange rate variable. Interest rate variables have a negative and significant effect on IDX Composite. Simultaneously it san be conclude that the independent variable. Inflation, exchange rate andinterest rate hae a significant effect on IDX Composite. Keywords : Inflation, Exchange Rate, Interest Rate, IDX Comosite